The clinical significance of procedural myocardial infarction in stable ischemic heart disease patients and implications for interpretation of Ischemia trial a registry analysis. (14th October 2021) - Das, S; Tran, Q; Moosavi, V; Itty, C; Farshid, A
Abstract: Background: The definition, incidence, and clinical significance of procedural myocardial infarction (MI) remains controversial. Interpretations from landmark trials such as "Ischemia" was found to be sensitive to the definition of procedural MI used (1). Purpose: Evaluation of the incidence of procedural MIs in our institution according to the standard definitions of Society of Cardiovascular Angiography & Intervention (SCAI) (2), Fourth Universal Definition of Myocardial Infarction (UDMI) (3) and Ischemia trial (4) and whether they predicted major adverse cardiovascular events (MACE) to validate clinical relevance of these definitions. Moreover, the study also explored the possibility whether HS-troponin alone could predict MACE thereby simplifying the definition of procedural MIs in the context of its wide-spread availability and its role as a standard biochemical marker of myocardial damage. Methods: We analysed ECGs, coronary angiograms and next day HS troponin-I results on consecutive patients who underwent elective percutaneous coronary intervention for stable Ischaemic Heart Disease during 2014–2018. Primary outcome was MACE including death, MI, stent thrombosis and need for repeat revascularisation within 12 months from index procedure. Results: We treated 909 patients with a mean age of 67.5 years and 78.4% were males. The proportion of patients in our cohort that met the troponin-based definition of procedural MI based on the Ischemia trial, SCAI and 4th UDMI were 10.1%, 6.3% and 25.1%. Occurrence of procedural MI according to these standard definitions were not predictive of MACE at 1 year (8.1% v 8.7% p=0.8; 11.1% v 8.5% p=0.5; 10.2% v 8.1%, p=0.3) (Table 1). The one-year MACE rate in the entire cohort was 8.5%. MACE rates were steady at troponin I levels below 2000 ng/L after which was there was a significant increase in MACE rates to 13.2% at troponin >2500, 19.1% for troponin levels >5000 and 33.3% for troponin>10, 000 ng/L. Conclusions: Procedural MI according to the Ischemia Trial definition was not predictive of MACE at 1 year, whereas troponin elevations above 2000 ng/L were associated with higher incidence of MACE in our cohort. These findings have significant implications for the interpretation of the Ischemia Trial. Moreover, potential of HS-troponin I level as a stand-alone and clinically relevant criteria for procedural MIs may be explored. Funding Acknowledgement: Type of funding sources: None.